The Strategy for Mubaligh Cadre Development by LDII at Nurul Hakim Kaliawen Islamic Boarding School in Kediri [Strategi Kaderisasi Mubaligh LDII di Pondok Pesantren Nurul Hakim Kaliawen Kediri] - Aly, Imam; Romadlon, Dzulfikar Akbar (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
The Nurul Hakim Kaliawen Islamic Boarding School focuses on training LDII preachers to become professional and religious preachers. This study explores these training strategies, emphasizing how the institution equips students with religious knowledge, noble character, and independence. Using a qualitative approach and descriptive analysis, data was collected through interviews, observations, and document studies, and analyzed using the Miles and Huberman method. The results show that Nurul Hakim Kaliawen implements the manqul-musnad-muttasil method in teaching the Qur'an and Hadith, instills the application of 29 noble characters, and promotes the development of independence. Regular evaluations are conducted to assess students' progress. In conclusion, the implemented training strategies have proven effective in shaping quality preachers and contributing to the development of students' competencies, while also providing additional insights into the effectiveness of training strategies in the context of LDII preaching. Abstrak Pondok Pesantren Nurul Hakim Kaliawen memfokuskan diri pada kaderisasi mubaligh LDII untuk membentuk mubaligh yang profesional dan religius. Penelitian ini mengeksplorasi strategi kaderisasi tersebut dengan menekankan cara lembaga ini membekali santri dengan pengetahuan agama, akhlakul karimah, dan kemandirian. Menggunakan pendekatan kualitatif dan analisis deskriptif, data dikumpulkan melalui wawancara, observasi, dan studi dokumentasi, serta dianalisis dengan metode Miles dan Huberman. Hasil penelitian menunjukkan bahwa Ponpes Nurul Hakim Kaliawen menerapkan metode manqul-musnad-muttasil dalam pembelajaran Al-Qur'an dan Hadits, serta membiasakan penerapan 29 karakter luhur dan pengembangan kemandirian. Evaluasi berkala dilakukan untuk menilai kemajuan santri. Kesimpulannya, strategi kaderisasi yang diterapkan terbukti efektif dalam membentuk mubaligh berkualitas dan berkontribusi pada pengembangan kompetensi santri, serta memberikan wawasan tambahan tentang efektivitas strategi kaderisasi dalam konteks dakwah LDII.